Direct regulation of Chk1 protein stability by E3 ubiquitin ligase HUWE1 - Cassidy, Katelyn B.; Bang, Scott; Kurokawa, Manabu; Gerber, Scott A. (The FEBS journal, 2020)
The HECT E3 ubiquitin ligase HUWE1 is required for a wide array of important functions in cell biology. Although HUWE1 is known to play a role in DNA damage signaling, the mechanism(s) that underlie this function remain elusive. HUWE1 regulates effectors of DNA replication and genotoxic stress tolerance. However, the loss of HUWE1 can also result in the accrual of significant endogenous DNA damage due to insufficient remediation of replication stress induced by an overabundance of key substrates. We discovered that HUWE1 depletion leads to a significant increase in levels of the single‐strand break effector kinase Chk1, independent of the DNA damage response, activation of apical DNA damage repair (DDR) signaling kinases (ATM and ATR), and the tumor suppressor p53. We also identified multiple lysine residues on Chk1 that are polyubiquitinated by HUWE1 in vitro, many of which are within the kinase domain. HUWE1 knockdown also markedly prolonged the protein half‐life of Chk1 in steady‐state conditions and resulted in greater stabilization of Chk1 protein than depletion of Cul4A, an E3 ubiquitin ligase previously described to control Chk1 abundance. Moreover, prolonged replication stress induced by hydroxyurea or camptothecin resulted in a reduction of Chk1 protein levels, which was rescued by HUWE1 knockdown. Our study indicates that HUWE1 plays a significant role in the regulation of the DDR signaling pathway by directly modulating the abundance of Chk1 protein. HUWE1 is a ubiquitin E3 ligase with a diverse array of known substrates. Amongst its cellular activities, HUWE1 is thought to play a key role in genome integrity and responses to DNA damage. Here, Scott Gerber and colleagues demonstrate that HUWE1 controls the stability of DNA damage response (DDR) effector kinase Chk1, via proteosomal degradation. Their data indicate that HUWE1 poly‐ubiquitinates Chk1, independent of the DDR. By directly regulating the stability of Chk1 protein in steady‐state conditions and under prolonged replication stress, HUWE1 plays a significant role in the regulation of the DDR signaling pathway.